2016
DOI: 10.1177/1082013216659610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high hydrostatic pressure and thermal processing on bioactive compounds, antioxidant activity, and volatile profile of mulberry juice

Abstract: The aim of this study was to investigate the effects of high hydrostatic pressure and thermal processing on microbiological quality, bioactive compounds, antioxidant activity, and volatile profile of mulberry juice. High hydrostatic pressure processing at 500 MPa for 10 min reduced the total viable count from 4.38 log cfu/ml to nondetectable level and completely inactivated yeasts and molds in raw mulberry juice, ensuring the microbiological safety as thermal processing at 85 ℃ for 15 min. High hydrostatic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Similar results were obtained by others. [5,7] Wang et al [7] found that Y&M were not detected in mulberry juice treated at 300 MPa/10 min, and the minimum holding times sufficient to produce mulberry juice with no detectable TAB was located at 500 MPa/10 min. According to Chen et al [5] , the Y&M were not detected in cloudy pomegranate juice, treated at 400 MPa/5 min, while the TAB were detected at 1.52 log 10 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar results were obtained by others. [5,7] Wang et al [7] found that Y&M were not detected in mulberry juice treated at 300 MPa/10 min, and the minimum holding times sufficient to produce mulberry juice with no detectable TAB was located at 500 MPa/10 min. According to Chen et al [5] , the Y&M were not detected in cloudy pomegranate juice, treated at 400 MPa/5 min, while the TAB were detected at 1.52 log 10 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The FPJ was processed using the method described by Wang et al [7] with slight modifications. For the HPP treatments, 40 mL of FPJ was poured into polyethylene/nylon vacuum bags (Huadun Plastics Co., Chengdu, China).…”
Section: Hpp and Tp Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations